(3GdOQ GdefXe aj GdGSe GdCYXes - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj dg GdCSeGA GdMSfi hHYO deG SFdJ Yf GdGSe GdCYXe heG hQO ajg aCQOJ Cf GJHY eG hQO ajg ef GdCMGOjK hGdBKGQ aCbhd aj GdGSe GdGYXe CbhGd s
(3BNQgG (B:s
(3ef WQjb Yj GHf LeGYI Yf GHf YHGS bGd (B" (3Cde (B" (3bSe CbSeg Gddg hgh ef CSeGFg JYGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 734s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds